The conversion of hydroxycinnamic acids into volatile phenols (in a synthetic media and in red wine) by Dekkera bruxellensis - Cabrita, Maria Joao (2012)
The conversion of p-coumaric acid, ferulic acid, and caffeic acid into 4-ethylphenol, 4-ethylguaiacol and 4-ethylcatechol was studied in Dekkera bruxellensis ISA 1791 under defined conditions in a synthetic medium and in a red wine. Liquid chromatography (HPLC-DAD) was used to quantify the phenolic acids, and gas chromatography (GC) coupled to a FID detector was used to quantify volatile phenols using a novel analytical methodology that does not require sample derivatization. Identification was achieved by gas chromatography-mass detection (GC-MS). The results show that phenolic acids concentration decreases while volatile phenols concentration increases. The proportion of caffeic acid taken up by Dekkera bruxellensis is lower than that for p-coumaric or ferulic acid; therefore less 4-ethylcatechol is formed. More important, 4-ethylcathecol synthesis by Dekkera bruxellensis in wine has never been demonstrated so far. These results contribute decisively to a better understanding of the origin of the volatile phenols in wines. The accumulation of these compounds in wine is nowadays regarded as one of the key factors of quality control.